2010
DOI: 10.1093/ndt/gfp747
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fibrosis and diastolic dysfunction in patients on chronic haemodialysis

Abstract: Our data support the hypothesis that, in a selected population of patients with ESRD undergoing haemodialysis, myocardial fibrosis is associated with LV diastolic myocardial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
0
36
0
4
Order By: Relevance
“…However, attempting to maintain the EOAI at more than 0.85 may have contributed to the good operative results. In most dialysis patients, diastolic function is impaired because of hypertrophied myocardium, myocardial fibrosis, and other toxic effects caused by hypertension, increased volume, and hyperparathyroidism [20,21]. Therefore, a higher EOAI in dialysis patients than that in nondialysis patients might be required for effective left ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, attempting to maintain the EOAI at more than 0.85 may have contributed to the good operative results. In most dialysis patients, diastolic function is impaired because of hypertrophied myocardium, myocardial fibrosis, and other toxic effects caused by hypertension, increased volume, and hyperparathyroidism [20,21]. Therefore, a higher EOAI in dialysis patients than that in nondialysis patients might be required for effective left ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…25,33, 34 Losi et al showed that myocardial fibrosis assessed using integrated backscatter signal but not LV mass index was independently associated with the presence of pseudonormal and restrictive patterns in 25 patients with ESRD undergoing HD. 5 This may suggest that LV fibrosis plays a central role in the development of LV diastolic dysfunction and the elevation of LV filling pressure in patients with ESRD on chronic HD. Importantly, MAC has been shown to affect mitral annular velocity and therefore may influence the assessment of a causal relationship between aortic valve narrowing and E/E'.…”
Section: Factors Of E/e'mentioning
confidence: 99%
“…We did not measure fibrosis; we used DD as a surrogate marker of myocardial fibrosis, which however correlates with fibrosis [44][45][46] . Fibrosis could be assessed with cardiac magnetic resonance, but the use of gadolinium in patients on dialysis is contraindicated.…”
Section: Discussionmentioning
confidence: 99%